Cytotoxic Effect of Recombinant Fragaceatoxin C on Peripheral Blood Mononuclear Cells - Leyla Darbarfard; Mehdi Imani; Seyyed Meysam Abtahi Froushani (Fasa University of Medical Sciences, 2020)
Background & Objectives: Actinoporins from sea anemones are potent pore-forming toxins. Fragaceatoxin C belongs to this family with a molecular weight of 20 kDa that mainly binds sphingomyelin in membranes and forming 2nm in diameter cation-selective pore. The aim of this study was the examination of recombinant toxin activity against peripheral blood mononuclear cells (PBMCs). Material & Methods: For recombinant expression of toxin, E.coli Bl21 was employed. The toxin purified by Ni2+-NTA Sepharose affinity chromatography. The purity of toxin was confirmed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis ) SDS-PAGE(. Various dilutions of the toxin were applied on red blood cells, and their hemolytic activity was analyzed by spectrophotometer by recording OD700. To examine the cytotoxic activity of purified toxin, PBMCs were treated with its different concentration. Cytolytic activity of FraC protein on PBMCs was measured using MTT and neutral red uptake assays. Results: Hemolytic assessment indicated that the toxin had retained its activity after purification. Analysis of PBMCs tests showed that low doses of toxin did not change the viability of cells compared to control cells. The metabolic activity of living PBMCs was only significantly decreased at the higher concentration (800 and 1000 NM) of the toxin. Despite the results of trypan blue tests, obtained data indicated that the Neutral red uptake assay was significantly reduced in PBMCs in a dose-dependent manner.  Conclusion: Despite toxicity against RBCs, FraC is not toxic to the peripheral blood mononuclear cells at lower doses.